Catalytic Reforming of n-Heptane on Platinum-Palladium Supported on g-Alumina - Vadi, Mehdi; Hosseinzade, Ali (Asian Journal of Chemistry, 2010)
The series of mono-metallic and bi-metallic catalysts have been prepared by imperegnating with solutions containing compound of H2PtCl6 and Pd(NO3)3 in 1 mL HCl (0.1 mol). The activity and selectivity of the catalysts have been determined under conditions at 450-500 °C and 15-30 atm. Molar ratio H2/C7H16 = 5 and for converting n-heptane. Under these experimental conditions it has been established that the conversion of n-heptane into branched aliphatic isomers is catalyzed by a bifunctional mechanism. The results show that when Pd is present, the catalysts are much more stable and have much higher selectivities for isomerization reaction. At high temperature the bimetallic catalysts produce much higher concentrations of cracked products. It is shown that Pd modifies the acidity of the support, resulting to higher selectivity for cyclization and lower selectivity for cracking and also modifies the properties of the platinum.